A demonstration of the conservation of the orbital angular momentum of Earth - Pellizza González, Leonardo Javier (2015)
We describe a simple but quantitative experiment to demonstrate the conservation of angular momentum. We measure the correlation of the apparent radius and angular velocity of the Sun with respect to the stars, due to the conservation of the angular momentum of Earth in its orbit. We also determine the direction of Earth?s angular momentum vector and show that it is conserved. The experiment can be performed using a small telescope and a digital camera. It is conceptually simple, allowing students to get direct physical insight from the data. The observations are performed near the resolution limit imposed by the atmosphere, and in the presence of strong competing effects. These effects necessitate a careful experimental setup and allow students to improve their skills in experimentation.